UPAYA MENINGKATKAN KEMAMPUAN MENYELESAIKAN MASALAH SOAL CERITA MATEMATIKA SISWA KELAS IV SD NEGERI KEPUTRAN A YOGYAKARTA DENGAN METODE ROLE PLAYING - Ahmad Agung Yuwono Putro (Universitas PGRI Yogyakarta, 2014)
This study is a class action consisting of 2 cycles. The subjects were 20 fourth grade students of SD Negeri Yogyakarta Keputran A. Object of this study is the overall process of learning math by using role playing in SD Negeri Yogyakarta Keputran A. The instrument of this study is the observation sheet implementation method of learning mathematics with role playing, observation sheets of students' ability to solve problems story, interview, test and test cycle 1 cycle 2. Results showed that the application of the method of role playing to improve Elementary School fourth grade students Keputran A Yogyakarta in solving mathematical word problems through the stages of (1) preparation, (2) implementation, (3) evaluation. The ability of fourth grade students of SD Negeri Yogyakarta Keputran A in solving mathematical word problems by using role playing to increase. This is shown by an increase in the ability to solve math word problems that students achieved before the measures in cycle 1 and after the action in cycle 2 by using role playing on learning mathematics, including, (a) the ability to write the data is known and ask questions based on the increase 61.91% to 82.95%, (b) the ability to plan a solution based on a matter increased from 5.48% to 68.35%, (c) the ability to solve problems increased from 42.86% to 60.98%, (d ) the ability to re-examine the truth of the answer is that it can interpret the answers that have been obtained in the context of the problem increased from 0% to 61.5%. In general, the ability of fourth grade students barnacle N 2 in solving mathematical word problems increased from an average of 50% prior to action on the cycle 1menjadi 70% after 2 cycles of action on the method of role playing on learning mathematics.